Pengaruh Penggunaan Media Quizizz Terhadap Minat Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan di Sekolah MTs Nurul Huda Timbang - Febriani, Juwita; Zakaria, Yoyo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of using the interactive learning media Quizizz on students' learning interest in the subject of Islamic Cultural History at MTs Nurul Huda Timbang. The method used in this study was a pre-experimental one-group pretest-posttest design. The sample size was 29 students in grade IX 3. The instrument used was a student learning interest questionnaire. Data analysis used a paired sample t-test. The results showed an increase in the average score of students' learning interest from 36.76 in the pretest to 39.59 in the posttest. The t-test obtained a significance value (sig. 2-tailed) of 0.005 < 0.05, indicating a difference in the average student learning interest before and after using Quizizz. Therefore, it can be concluded that the use of Quizizz media has an effect on the subject of Islamic Cultural History at MTs Nurul Huda Timbang.